2007
DOI: 10.1002/cphc.200700426
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Na* Emission and “Chemically Active” Acoustic Cavitation Bubbles

Abstract: The emission from electronically excited sodium atoms (Na*) from aqueous solutions containing NaCl or sodium dodecylsulfate under ultrasonic irradiation is studied. Evidence is presented that strongly suggests Na* emission arises from a population of bubbles that are sonochemically active but not producing sonoluminescence (SL). Results indicate that the Na* emission intensity is mainly dependent on the concentration of Na(+) ions near the bubble/solution interface. The results provide further insight into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 29 publications
4
33
0
5
Order By: Relevance
“…Similar observations have been reported for Na salts and SDS in water [35,36,37,38,39]. The emission of alkali metal lines itself [40,41] is a phenomenon that gives important information on the collapse modalities of the emitting bubbles.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar observations have been reported for Na salts and SDS in water [35,36,37,38,39]. The emission of alkali metal lines itself [40,41] is a phenomenon that gives important information on the collapse modalities of the emitting bubbles.…”
Section: Introductionsupporting
confidence: 74%
“…Due to negligible vapour pressure, the metal atoms should be virtually absent in the "pure" bubble interior gas phase before collapse. Reduction of the ions and excitation could only occur either in the hot "liquid shell" of the collapsed bubble [42], or from "injected droplets" of liquid entering the gas phase [43,35,23]. A potential micro spray would (fully or partly) evaporate with subsequent thermolysis, reduction, and excitation of the metal in the heated (and possibly plasma) environment inside the bubble.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies [26,27] have shown that both SL and SC activities originate from two different bubble populations. It was shown that more SL bubbles were generated at the surface of the liquid, whereas the sonochemically active bubbles were observed in a relatively wider area.…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…Figure 2 shows a new result demonstrating the influence of surfactant on the shape of Na line in SL spectra. Earlier it was reported that small amount of surfactant leads to the growth of intensity of Na line, as well as in a case of large concentration of salt [14]. It was also calculated that the thickness of a salt-solution layer of about 16 nm near bubble boundary is enough for explanation of Na line intensity [15].…”
Section: Resultsmentioning
confidence: 99%